Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This edited book presents the scientific outcomes of the 19th IEEE/ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD 2018), which was held in Busan, Korea on June 27-29, 2018. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. The book includes research findings on all aspects (theory, applications and tools) of computer and information science and discusses the practical challenges encountered along the way and the solutions adopted to respond to them. The book includes 13 of the conference's most promising papers.
Impact of Transactive Memory Systems on Team Performance and the Moderating Effect of Joint Decision Making -- Customers' Continuous Usage Intention of Virtual Reality (VR) Product -- A Study on The Method of Removing Code Duplication Using Code Template -- ICBM-based Smart Farm Environment Management System -- Design of I-beacon based distribution route management system to prevent the spread of Livestock disease -- Optimal energy management system design for Smart Cattle shed -- A new polynomial algorithm for Cluster Deletion problem -- A Study on the Lie Detection of Telephone Voices Using Support Vector Machine -- A Study on the Factors Affecting a Switch to Centralized Cloud Computing for Local Government Information System -- An efficient technique of detecting program plagiarism through program slicing.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence